Studies of Anticoagulant Therapy in Frail Elderly Patients: Problems of Terminology and Methodology - Sergey N. Bel'diev; Irina V. Medvedeva; Dmitry Yu. Platonov; Galina Yu. Trufanova (Столичная издательская компания, 2019)
A recently published article (Rational Pharmacotherapy in Cardiology 2018;6:908-16) on the problems of anticoagulant therapy in patients with frailty syndrome contains two statements which highlight rivaroxaban among other non-vitamin K antagonist oral anticoagulants (NOAC): 1) none of the randomized controlled trials (RCTs) with NOAC (except for two RCTs with rivaroxaban - EINSTEIN-DVT and EINSTEIN-PE) contained data on the participation of frail patients; 2) one of the studies of real clinical practice showed that only therapy with rivaroxaban (out of three NOAC) in comparison to warfarin reduced the risk of stroke / systemic embolism and ischemic stroke in frail elderly patients with atrial fibrillation after 2 years of observation. The paper presents a critical analysis of these statements showing that the first statement is based on the incorrect use of the collective term "fragility" as a synonym for the term "frailty", whereas the second statement is based on the results of a study that has a number of serious methodological limitations.